AI-powered chatbots in recruitment from Indian HR professionals’ perspectives: Qualitative study - Tuffaha, Mohand; Pandya, Bharti; Perello-Marin, M Rosario (The journal of contemporary issues in business and government, 2022)
Although artificial intelligence (AI) is broadly extended worldwide, full potential is not being reached in human resource management (HRM) so far. In fact, there is still a gap in analyzing the usefulness and limitations of chatbots in recruitment. This piece of research attempts to cover part of this gap paying particular attention to the Indian market. A qualitative analysis has been undertaken in selected Indian companies. One of the main conclusions drawn from the study is the need for mature chatbots in recruitment. Although chatbot has several features from HR professionals’ perspectives, our paper reveals that chatbot has particular limitations in hiring mid-level and senior-level positions. Furthermore, there is a gap between what are Indian IT companies offering for recruiters and what are recruiters know about the latest development of the chatbots. The paper contributes as a food for thought for HR managers and academia by provides an extensive analysis of the usefulness and limitations of chatbots in the recruitment process in India.